Genetic Diversity and Prevalence of Leishmania mexicana in Bichromomyia olmeca olmeca 1 in an Endemic Area of Mexico - Pasos Pinto, Silvia (2017)
Leishmaniases are endemic in southwestern Mexico, and different sand fly species are infected with Leishmania mexicana Biagi. One of the most abundant vectors and dominant species is Bichromomyia olmeca olmeca (Vargas and Díaz-Nájera). We analyzed the genetic variability of Bichromomyia olmeca olmeca and the prevalence of Leishmania mexicana infections with an endemic focus: "the Ejido 20 de Junio" (Mancolona), Campeche, Mexico, where patients with leishmaniases are reported throughout the year. Genetic diversity analysis of 102 sequences of a 270-bp fragment of the 3 end of mitochondrial cytochrome b (cyt b) gene of Bichromomyia olmeca olmeca revealed 17 haplotypes. The nucleotide diversity and nucleotide polymorphism index were low. The neutrality test and Mismatch test showed population expansion. Prevalence of Leishmania mexicana was 24.5% in 102 females analyzed. This is the first study showing the genetic diversity of Bichromomyia olmeca olmeca sand flies in the Campeche region of Mexico, and also provides novel information on the high infection rate of Bichromomyia olmeca olmeca by Leishmania mexicana. Our finding of high sand fly infection rates during the end of the dry and hot weather of July enriches the literature because high infection rates had been reported only during the rainy season (November) in the region.